2021
DOI: 10.1093/femsle/fnab063
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of camellia oil ameliorates obesity and modifies the gut microbiota composition in mice fed a high-fat diet

Abstract: Obesity, which is often caused by adipocyte metabolism dysfunction, is rapidly becoming a serious global health issue. Studies in the literature have shown that camellia oil (camellia oleifera Abel) exerted potential lipid regulation and other multiple biological activities. Here, we aimed to investigate the effects of camellia oil on obese mice induced by a high-fat diet and to explore gut microbiota alterations after camellia oil intervention. The results showed that oral administration of camellia oil drama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Despite the biological meaning of all of these gut microbiota modifications induced by cuticle supplementation is unclear, similar changes in several of these bacterial populations (increases of Prevotellaceae, Bifidobacteriaceae and Coriobacteriaceae, decrease of Desulfovibrionaceae) are in line with those found in other obese rodent models, in which antisteatotic and hepatoprotective effects have been observed. 49,50 Thus, the observed beneficial modifications of the microbial community induced by the insects’ cuticles are likely relevant with regard to the strong antisteatotic effect observed in the present study. Regarding that obesity-induced dysbiosis plays a key role for fatty liver development through impairing the integrity of the intestinal barrier and feeding the insects’ cuticles counteracted some of the obesity-induced changes in the gut microbiota composition ( e.g.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Despite the biological meaning of all of these gut microbiota modifications induced by cuticle supplementation is unclear, similar changes in several of these bacterial populations (increases of Prevotellaceae, Bifidobacteriaceae and Coriobacteriaceae, decrease of Desulfovibrionaceae) are in line with those found in other obese rodent models, in which antisteatotic and hepatoprotective effects have been observed. 49,50 Thus, the observed beneficial modifications of the microbial community induced by the insects’ cuticles are likely relevant with regard to the strong antisteatotic effect observed in the present study. Regarding that obesity-induced dysbiosis plays a key role for fatty liver development through impairing the integrity of the intestinal barrier and feeding the insects’ cuticles counteracted some of the obesity-induced changes in the gut microbiota composition ( e.g.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, an increased abundance of Actinobacteria in the gut has been reported to be associated with antisteatotic and antiinflammatory effects of different dietary interventions (fucoidan polysaccharides, camellia oil) in rodent models of obesity and steatosis. 49,50 The increased abundance of Actinobacteria in group O3.0 was attributed to dramatic increases of two bacterial families, namely Bifidobacteriaceae and Coriobacteriaceae represented exclusively by the genera Bifidobacterium and Olsenella , respectively, in the gut microbiota of the obese rats. While many probiotic Bifidobacterium strains are well-documented to attenuate hepatic steatosis and inflammation in rodent models of fatty liver disease, 51,52 an increased abundance of Coriobacteriaceae and its genus Olsenella in obese mice was found to be associated with antiobesity effects of Artemisia polysaccharides 53 and has been hypothesized to be responsible for hepatoprotective and antisteatotic effects of camellia oil in diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assay For The Brain Content Of Gaba In Sodium Pentobarbital-treated Mice Brain samples were collected as previously described [11]. Brie y, the brain samples were homogenized with ice-cold sodium chloride solution (w/v, 1:9).…”
Section: Test On the Prolonged Duration Of Sodium Pentobarbital-induc...mentioning
confidence: 99%
“…16,17 An appropriate amount of CO administered by intramuscular injection or gavage reduced the cholesterol concentration in the serum of CCl 4 -induced oxidative damage rats, decreased the serum triglyceride content of hyperlipidemic mice and increased the triglyceride content in the blood lipids of normal mice. 18,19 It was demonstrated that CO could significantly decrease the ratio of saturated fatty acid to unsaturated fatty acid content in patients with hyperlipidemia, and thus regulate the metabolism of lipids in the body and lower blood lipid levels. 20 The human and animal intestines are colonized by a large microflora.…”
Section: Introductionmentioning
confidence: 99%